Production, characterization, and antitumor efficiency of l-glutaminase from halophilic bacteria - Eman Zakaria Gomaa (Bulletin of the National Research Centre, 2022)
Abstract Background Halophiles are an excellent source of enzymes that are not only salt stable, but also can withstand and carry out reaction efficiently under extreme conditions. l-glutaminase has attracted much attention with respect to proposed applications in several fields such as pharmaceuticals and food industries. The aim of the present study was to investigate the anticancer activity of l-glutaminase produced by halophilic bacteria. Various halophilic bacterial strains were screened for extracellular l-glutaminase production. An attempt was made to study the optimization, purification, and characterization of l-glutaminase from Bacillus sp. DV2-37. The antitumor activity of the produced enzyme was also investigated. Results The potentiality of 15 halophilic bacterial strains isolated from the marine environment that produced extracellular l-glutaminase was investigated. Bacillus sp. DV2-37 was selected as the most potent strain and optimized for enzyme production. The optimization of fermentation process revealed that the highest enzyme activity (47.12 U/ml) was observed in a medium supplemented with 1% (w/v) glucose as a carbon source, 1% (w/v) peptone as a nitrogen source, 5% (w/v) NaCl, the initial pH was 7.0, at 37 °C, using 20% (v/v) inoculum size after 96 h of incubation. The produced crude enzyme was partially purified by ammonium sulfate precipitation and dialysis. Of the various parameters tested, pH 7, 40 °C, and 5% NaCl were found to be the best for l-glutaminase activity. The enzyme also exhibited high salt and temperature stability. The antitumor effect against human breast (MCF-7), hepatocellular (HepG-2), and colon (HCT-116) carcinoma cell lines revealed that l-glutaminase produced by Bacillus sp. DV2-37 showed potent cytotoxic activity of all the tested cell lines in a dose-dependent manner with an IC50 value of 3.5, 3.4, and 3.8 µg/ml, respectively. Conclusions The present study proved that l-glutaminase produced by marine bacteria holds proper features and it has a high potential to be useful for many therapeutic applications.